Implementation of Education Management in Improving the Education Quality of SLB B-C Cahaya Bangsa Karawang - Ujang Cepi Barlian; Syarip Hidayat Sutisna; Abdul Rojak; Wahyu Rananda Saputra (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2023)
This study aims to determine the implementation of special education management in special schools for children with autism. This research is a descriptive qualitative research. The sources for this study were the principal and two teachers at SLB Cahaya Bangsa Karawang. Data collection is done by interview, observation, and documentation. Data analysis techniques use the Miles and Huberman models. There are three steps in this model, namely data reduction and drawing conclusions. The implementation of special education management in SLB is coordinated by the school principal. In planning an educational program, it is adjusted to the abilities of each autistic student using the IEP (Individual Education Program). The school has an organizational structure that works according to its duties. The principal is in charge of coordinating school management, while the teacher is responsible for classroom management. Special Schools (SLB) are newly established schools. The condition of autistic students who have different conditions, the location of the foundation's office and the school which is quite far away, and the entry of students with different conditions from autistic students make the implementation of education management in SLB not run optimally. Therefore, the school has made efforts to minimize these obstacles.